Antimicrobial therapeutic enhancement of levofloxacin via conjugation to a cell‐penetrating peptide: An efficient sonochemical catalytic process. (29th July 2020) - Taheri‐Ledari, Reza; Maleki, Ali
Abstract : Herein, we make an effort to enhance the antimicrobial activity of levofloxacin (LVX) antibiotic via conjugation to a cell‐penetrating peptide (CPP) including Cys‐Gly‐Ala‐Phe‐Pro‐His‐Arg. For this purpose, cysteine is used as a linker between the LVX and CPP chain, and two heterogeneous nanoscale catalytic systems are employed as the substantial alternatives for traditional peptide coupling reagents like N, N, N ′, N ′‐tetramethyl‐O‐(benzotriazol‐1‐yl)uronium tetrafluoroborate (TBTU). Briefly, it has been found out that the antimicrobial potency of the synthesized CPP‐LVX conjugate (on the gram‐positive and gram‐negative bacteria) is noticeably enhanced ( 20% more). It has been revealed via zone of inhibition (ZOI) and optical density (OD) evaluations. As a convenient method for making this type of the effective conjugations, ultrasound waves (with a specific frequency and power density) activate the catalytic sites of the heterogeneous nanoparticles. Through this synergistic effect, peptide/amide bond is formed during a short time (10 min), and high reaction yield (>90%) is obtained under mild conditions. Moreover, as a simple purification process, the catalyst nanoparticles are collected and separated through their high magnetic property. Abstract : Convenient and fast synthesis of levofloxacin‐cell penetrating peptide conjugation by two heterogeneous magnetic catalytic systems.